Structure Optimization and Performance Simulation of a Double-Disc Fertilizer Spreader Based on EDEM-CFD - Mingxiong Ou; Guanqun Wang; Ying Lu; Zhengji Zhang; Huijie Pan; Weidong Jia; Xiang Dong (Agronomy)
To address practical issues, such as uneven fertilizer distribution and poor particle dispersion, during the operation of a centrifugal double-disc fertilizer spreader, a discrete element method (DEM) simulation was initially performed. In this simulation, the blade inclination angle, fertilizer discharge offset angle, and spreading height were selected as experimental factors. The spreading width and the coefficient of variation (Cv) of fertilizer uniformity served as evaluation indicators. A quadratic orthogonal simulation experiment was designed to evaluate spreading performance. Subsequently, regression equations were established to optimize parameters and determine the optimal design configuration. Experimental results showed optimal performance with a blade inclination angle of −5°, fertilizer discharge offset angle of 45°, spreading height of 1050 mm, and disc rotational speed of 400 rpm. Considering that fertilizer spreaders are susceptible to air resistance and environmental wind during field operations, an EDEM-CFD coupling method was employed to simulate realistic operating conditions. Virtual simulation results demonstrated optimal fertilizer spreading performance at disc rotational speeds ranging from 350 to 400 rpm under tailwind conditions, and from 400 to 500 rpm under headwind conditions. Based on the simulation results, a prototype was built and tested. The experimental results closely matched the simulation predictions, thereby confirming the effectiveness of the simulation model. This study provides valuable insights and serves as a reference for designing and optimizing fertilizer spreader performance under practical operational conditions.